1978
DOI: 10.1007/bf00420990
|View full text |Cite
|
Sign up to set email alerts
|

A special thermal stress problem in ceramic industry

Abstract: While surveying the hygienic conditions in small to medium ceramic industries, it was noted that an acute thermal stress problem existed in kiln unloading operations being performed manually. A more detailed investigation of this problem in four typical ceramic factories confirmed that the thermal conditions imposed severe stress on the workers with WBGT values ranging between 43 and 54 degree C inside the kiln. However, the physiological strain experienced by even the workers who remain inside the kiln for un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In an actual work setting, Miller et al (2011) reported that "few workers will voluntarily work at a pace that requires sustaining an average heart rate >110 bpm for any length of time". Similarly, Parikh et al (1978) found that ceramic workers automatically adjust their pace of work under heat stress such that no cumulative risk is found in workers' heart rate record throughout a work shift. This mechanism is expected to lead to a natural reduction in labour productivity (Miller, et al, 2011).…”
Section: Self-paced Work On Construction Sitesmentioning
confidence: 99%
“…In an actual work setting, Miller et al (2011) reported that "few workers will voluntarily work at a pace that requires sustaining an average heart rate >110 bpm for any length of time". Similarly, Parikh et al (1978) found that ceramic workers automatically adjust their pace of work under heat stress such that no cumulative risk is found in workers' heart rate record throughout a work shift. This mechanism is expected to lead to a natural reduction in labour productivity (Miller, et al, 2011).…”
Section: Self-paced Work On Construction Sitesmentioning
confidence: 99%